The 2023 Mw 7.8 Kahramanmaraş earthquake rupture increases potential failure along the northern Dead Sea Fault - Meghraoui, Mustapha; Cakir, Ziyadin; Kariche, Jugurtha; Toussaint, Renaud; Provost, Floriane; Karabacak, Volkan; Sbeinati, Reda Mohamed; Altunel, Erhan; Nemer, Tony (Elsevier BV, 2025)
Field observations conducted immediately following the February 6, 2023, Mw 7.8 Kahramanmaraş earthquake documented the southern surface rupture termination in the Amik Basin. The termination occurred in an en-echelon pattern, extending across the 3.5 km width of the approximately 10-km-wide stepover. This extension reached towards the northern tip of the Hacıpaşa Fault, which constitutes the main northern segment of the Dead Sea Fault Zone (DSFZ). Archaeoseismologic and paleoseismologic data show that the approximately 800-km-long DSFZ has been seismically quiet for more than 600 years in the north and 900 years in the south. A similar fault connection geometry at the western end of the 1939 Ms 7.9 Erzincan earthquake in the easternmost part of the North Anatolian Fault Zone and the subsequently triggered successive large magnitude earthquakes migrating westward within a few decades highlights an increased seismic hazard for the entire DSFZ. This heightened seismic hazard potential along the DSFZ, combined with historical population centers experiencing wars and migrations, puts millions of people at an unparalleled risk.
Keywords: [SDU] Sciences of the Universe [physics]; Stress transfer modelling; East Anatolian Fault; [SDU.STU.TE] Sciences of the Universe [physics]/Earth Sciences/Tectonics; Dead Sea Fault; earthquake sequence; Southern migration